THE CONSEQUENCES OF REVISIONISM ON THE APPLICATION OF CABOTAGE PRINCIPLE IN THE INDONESIAN MARITIME LAW - Marco Bastian Lumentah; Adhitya Nini Rizki Apriliana (Department of Law, Faculty of Law, University of Mataram, 2026)
Historically, the Cabotage Principle is no recent concept in the history of Indonesia, albeit the contemporary re-emergence nuanced a problem for the national maritime industry and the legal system itself. This normative research tries to tackle this problem with a critical theory approach, by not only relying on doctrinal techniques, but also political economy, literary, and ethical concepts to find anomalies before inferring to the best explanation. After studying the four main Acts and several derivate regulations along with their practice in the real world, through concepting the three modes of moral claim, the research finds various dissonance and irregularities, indicating a non-compliance which may result from preferential institutional praxis of the law. Investigating from multiple cases, the diagnosis is of post-modernism: the value dissonance is symptomatic of a deeper institutional decay and instability which can at least be traced back to the year 2014, purporting of the principle’s values, and aided by legal discrepancies resulting in the undeveloped goal of the initiated principle. The effects of the revisionism on the application of cabotage principle in the Indonesian maritime law are diverse and we can at least come into conclusion of a hypothesis on what hinders the principle’s goals. The author recommends to reverse several amendments, revitalize the original ontology of the 2008 Shipping Act, and replacement of the 32 Marine Act of 2014, also the re-establishment of DEKIN to ensure the archipelagic outlook of Indonesia is preserved with the utmost importance in the nation’s economic, social, cultural, and political life.